2011
DOI: 10.1007/s11910-011-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Naming and the Role of the Uncinate Fasciculus in Language Function

Abstract: In this paper, an overview of the studies relating naming to the uncinate fasciculus is reported. With the introduction of contemporary neuroimaging techniques, namely of diffusion tensor imaging, white matter tracts have been investigated more thoroughly and possible changes in the uncinate fasciculus integrity have been correlated to different neuropsychological deficits. Although previous research has proposed a role of the left uncinate fasciculus on action and object naming or in semantic processing, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 45 publications
4
43
1
1
Order By: Relevance
“…The empirical validity of this proposal needs to be qualified, however, by the observation that the UF has been linked to language functions (naming) only in a small number of studies [66, 67]. Others have found that resection of the UF has limited effects on the long-term language functions, such as sentence processing (e.g., [68]) and semantic processing (e.g., [69]).…”
Section: Models Of Functional Neuroanatomy Of Language: From Lesiomentioning
confidence: 99%
“…The empirical validity of this proposal needs to be qualified, however, by the observation that the UF has been linked to language functions (naming) only in a small number of studies [66, 67]. Others have found that resection of the UF has limited effects on the long-term language functions, such as sentence processing (e.g., [68]) and semantic processing (e.g., [69]).…”
Section: Models Of Functional Neuroanatomy Of Language: From Lesiomentioning
confidence: 99%
“…15 Interruption of white matter connections has been associated with language impairments. For example, surgical resection of the left uncinate fasciculus has resulted in impaired naming and verbal fluency, 16 and isolated damage to the corpus callosum within callosotomy patients can result in a naming impairment. 17 Studies of traumatic brain injury (TBI) patients have shown that white matter pathways are susceptible to damage from head trauma.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The degree of directionality of water diffusion is quantified as a scalar value, fractional anisotropy (FA), that distinguishes between abnormal and healthy white matter based on the cylindrical patterns of the diffusion. White matter pathway disruption as assessed by FA has been correlated with performance on some neuropsychological tasks, 16,29,30 including naming performance. 31 Professional football players who experienced subconcussive head impacts 32,33 may be susceptible to increased risk for progressive cognitive decline and affective disorders 34,35 with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the ventral route is composed of a complex network of white matter fiber bundles, mainly consisting of the inferior longitudinal fasciculus (ILF), the inferior fronto-occipital fasciculus (IFOF) and the uncinate fasciculus (UF). These fiber bundles connect the frontal, temporal and occipital cortices (Papagno, 2011; Axer et al, 2013; Menjot de Champfleur et al, 2013; Chan-Seng et al, 2014; Motomura et al, 2014; Chang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%